Understanding Children and Childhood : a New Zealand Perspective. - Smith, Anne B. (Bridget Williams Books, 2013)
Understanding Children and Childhood examines how and why children develop, and how they interact with the people and events in their lives. Anne Smith's multi-disciplinary perspective helps build a flexible understanding of childhood in New Zealand.